Africa yam breeding for impact 2017 - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2018)
The yam breeding activities at IITA Abuja station involves hybridization to generate variability, seedling and tuber progeny generation at the screen house and in the field to select superior plants with trait of interest.